Conservation of Selected Rare and Endemic Trees from Northern Western Ghats - Deshpande, Swapnaja M.; Yadav, Shrirang R. (Indian Forester, 2020)
Biodiversity is a measure of health of ecosystem and climate. Due to various anthropogenic activities merely for economic and human made capital there is serious threat to natural capital. In order to sustain the natural resources and ultimately human survival. It is essential to adopt different approaches for management and conservation of biodiversity. In present investigation an attempt has been made for conservation of some rare and endemic tree taxa through development of nursery techniques. Twenty tree taxa were studied for their seed behavior, germination and conservation. It offers an important method for the conservation and sustainable utilization of bioresources from these forest trees.